A Rare Triple Neural Tube Defect- Case Report - Kumar, Amit; Kumar, Kislay (Nepal Journal of Neuroscience, 2023)
Multiple neural tube defects are a rare entity and it also includes anomalies like encephalocele, dermal sinus, myelomeningocele, and spina bifida. These occur due to defective closure of neural tube at multiple sites. There have been isolated cases of coexistence of triple neural tube defect in same subject and only 9 cases have been reported in available world literature. Here, we present a rare case of 7 days old boy with three different NTDs- occipital encephalocele, upper cervical meningocele and lumbar myelomeningocele. Type II Chiari malformation, tethered cord, fenestration of posterior falx, hydrocephalus and syringohydromyelia accompanying the NTDs.